A Cross – Sectional Study Between The T2DM and Abnormal Lipid Profile in Al- Musayyib City - Omran, Zahraa Sabbar (Scientific Journal of Medical Research, 2020)
Background: Diabetes mellitus (DM) is a disorder of the abnormal metabolic that diagnosed by elevated the glucose level in the blood. Patients with (NIDDM) are frequently affected by atherosclerotic vascular disease . There are some factors that Contribution to swifter atherosclerosis, these factors include dyslipidemia, hypertension, smoking, obesity and insulin resistance. Objectives: The aim of this study is determine lipid profile in the patients with diabetes mellitus. Methods: We estimation the level of glucose in the patient with ( NIDDM ) and lipid profile (TC, T.G., LDL, HDL and vLDL).The patients were fasting for 12 hours. Results: We found the elevated level of T.G., cholesterol and LDL, but the level of HDL was decreased. Positive significant between the T.G. with (LDL, vLDL) in both gender and cholesterol with (LDL and T.G.) but negative significant between HDL with LDL in man but in woman the HDL with ( CHO., T.G. , LDL and vLDL). Conclusion: We show in this study elevated lipid profile in patients with NIDDM , Therefore, the chances of developing atherosclerosis are clearly increased and can be eliminated by using therapeutic methods in addition to weight loss, physical activity to reduce elevated the lipid profile especially (T.G. and LDL).